Estimativa de carga limite de serviço em placas CLT: desenvolvimento de equação e software - Silva, Guilherme dos Santos (2025)
The industrialized product Cross Laminated Timber (CLT), with wood as its primary raw material, serves as a competitive structural element compared to conventional reinforced concrete slabs. As a result, the proliferation of manufacturers producing this element in several countries is already a reality. Given that the current calculation methods for CLT in standards documents are one-dimensional and do not adequately capture its complex behaviour, a software for structural analysis of CLT panels and regression models (classical and symbolic approach) for estimating the load in service condition in a two-dimensional approach are proposed. This equation was made possible through a parametric study varying the geometric properties of the panel (length, width, veneer configuration) followed by simulations performed in the software itself. The developed software presented is reliable with small percentage differences (from 0.004% to 3.452%) in the displacement, main forces and stresses, when compared to similar software. The proposed best-fit equation, obtained by the symbolic regression model, presented adequate accuracy in estimating the service limit load, achieving a coefficient of determination (R²) equal to 99.996%. Therefore, the simplicity of the models combined with their excellent accuracies provide engineers with insights for better pre-desing of CLT panels.